Plant nanocellulose and its composite hydrogel membranes-based polyvinyl alcohol/hyaluronic acid for biomedical applications: Extraction, characterization, and in vitro bioevaluation - Yasmein Hussein, Elbadawy A. Kamoun&, Samah A. Loutfy&, Rehab Amen, Tarek H. Taha, Ahmed S. Mansour, Ahmed I. Abdel-Salam, Mahmoud Amer (Journal of Applied Pharmaceutical Science, 2021)
Needle-like cellulose nanocrystals (CNCs) were prepared from useless rice straw, which posed problems of environmental pollution in Egypt during its disposal in the burning process. Cellulose was obtained using an alkaline treatment, followed by a bleaching process and acid hydrolysis producing a high yield of CNCs ~12 ± 3 (%, w/w). Resultant CNCs were instrumentally characterized by FTIR, XRD, transmission electron microscopy (TEM), Brunauer–Emmett–Teller, and particle potential analyses; moreover, antimicrobial activity, hemolysis, and cytotoxicity were bioassessed. XRD exhibited an elevated crystallinity index of approximately 98%, and thermal decomposition of thermogravimetric analysis thermograph ranged from ~245 to 480°C. The TEM investigation showed that the nonaggregated needle-like nanocrystals diameter ranged from ~20 to 60 nm. Interestingly, CNCs at high concentrations (1,000 μg/ml) did not affect the viability of HFB-4 and WI38 human normal cell lines. Polyvinyl alcohol (PVA)/hyaluronic acid (HA) hydrogel membranes were reinforced with various concentrations of CNCs [0.25, 0.5, and 1.0% (w/v)] and prepared by the solution-casting method using citric acid as a crosslinker. The results revealed that using CNCs as nanofillers up to 0.5% enhanced dramatically the mechanical properties of membranes and exhibited good swelling capacity, biocompatibility, and antimicrobial activity, compared to hydrogel free CNCs. Therefore, the PVA/HA/CNCs membranes might have great potential in wound dressing application and it can be regarded as suitable to be developed into targeted nanocarriers or nanofillers for biomedical applications.
Keywords: Cellulose nanocrystals, extraction, PVA/hyaluronic acid, composite hydrogel membranes, bioevaluation tests.